ANALISIS KINERJA PRODUKSI INDUSTRI KECIL ROKOK KRETEK DI KABUPATEN KUDUS - Rizka Rahman (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2014)
Kudus regency is one of the regencies in Central Java which is well known of its industrial sector in small, medium, as well as in large scale. Clove cigarette is one of the large industrial sectors in Kudus. However, in 2008 until 2010 the production of cigarette decreased. It can be seen from the declining of the production of hand-made clove cigarette and also factory clove made cigarette. The statement of problem in this study is how much the effect of fund, employee, and raw materials toward the products produced by small scale clove cigarette industry in Kudus regency. The data are analyzed by using percentage descriptive method and multiple regressions using computer program eviews. The result of the study showed that simultaneously variable of fund, employee, and raw materials used at once influences the cigarettes produced in Kudus regency. While, simultaneously variable of fund and raw materials influences significantly to the product, and variable of employee is not significantly influenced. In conclusion, 84.2% of the models are able to explain dependent variable and the rest is influenced by other factors except for the analyzed models.